Antimicrobial Resistance and Molecular Epidemiology of Uropathogenic Escherichia coli Isolated From Female Patients in Shanghai, China - Zeng, Qian; Xiao, Shuzhen; Gu, Feifei; He, Weiping; Xie, Qing; Yu, Fangyou; Han, Lizhong (Frontiers in Cellular and Infection Microbiology, 2021)
Urinary tract infection (UTI) is one of the most common bacterial infections and UTI is the most common extraintestinal infectious disease entity in women worldwide. Uropathogenic Escherichia coli (UPEC) is the leading cause of UTI. While antimicrobial resistance has emerged as one of the principal problems of UTI, little is known about the epidemiology of UPEC isolated from female patients in Shanghai. This study aimed to describe the antimicrobial resistance and molecular epidemiology of UPEC isolated from female patients in Shanghai, China. UPEC isolates were collected from female patients from July 2019 to June 2020 in Shanghai and a total of 151 isolates were obtained randomly. Antimicrobial susceptibility testing was performed using the disk diffusion method. Multilocus sequencing type, phylogenetic groups, antimicrobial resistance genes, and virulence genes were detected by polymerase chain reaction. In our study, no carbapenem-resistant isolates were found, but fluoroquinolone-resistant and multi-drug resistant UPEC accounted for 62.25% and 42.38%, respectively. The phylogenetic group B2 (58.94%) predominated, followed by phylogenetic group D (26.49%). The most prevalent sequence type was ST1193 (25.83%), which was first reported in Shanghai. The rate of extended-spectrum β-lactamase (ESBL)-positive isolates was 39.74% and the dominant ESBL genotype was blaCTX-M-14 (21/60), followed by blaCTX-M-55 (12/60). Mutations in gyrA were detected in the majority of fluoroquinolone-resistant isolates (90/94), followed by parC (85/94) and parE (71/94). The aac (3) -IIa was also found in 85% of aminoglycoside resistance isolates. Among 151 UPEC isolates, the common virulence genes were csgA (97.35%), fimH (92.72%), sitA (82.12%), and malX (65.56%). In conclusion, the high antimicrobial resistance of UPEC isolated from female patients, harboring a series of virulence genes, are troublesome for medical practitioners in Shanghai. At present, the prevalent ST1193 and emerging blaCTX-M-55 make UTI therapy more challenging.